REGULATION OF RENEWABLE ENERGY TARIFF IN THE NIGERIAN ELECTRICITY SUPPLY INDUSTRY (2023)
Nigeria depends on fossil fuel-based source of electricity. Despite abundant renewable energy resources endowment, it has failed to harness and deploy that into the national grid for boosting electricity generation and the country achieving the target energy-mix in the power sector. The Nigerian Electricity Regulatory Commission (NERC) issued Regulations on Feed In Tariff (REFIT) for Renewable Energy Sourced Electricity in 2015, pursuant to which 13 Power Purchase Agreements (PPA) were executed in 2016. Notwithstanding the intendment of the government policies, the REFIT and the PPAs have not materialised. Existing studies on the REFIT 2015 have not examined the legal issues responsible for the non-implementation of the 13 PPAs. This study therefore, examined the legal and contractual ramework for REFIT in Nigeria. Public Interest Theory provided the framework, while doctrinal and qualitative methods were adopted. Primary data were obtained from the Constitution of the Federal Republic of Nigeria 1999 (Sections 12, 14 and 16), Electric Power Sector Reform Act (EPSRA) 2005, REFIT Regulation 2015, NERC Multi Year Tariff Order 2008 and 2012 and the PPAs. Key informant interviews were conducted with two of officials of NERC (Manager Legal and Licencing Unit), and one each of Nigerian Bulk Electricity Trading Company (General Counsel) and the Independent Power Producers (IPPs) (Legal Officer, Anjeen Solar). Legal analyses were drawn from the Constitution and the EPSRA, while a narrative approach based on the thematic area of renewable electricity was used to analyse the qualitative data. Data were subjected to content and jurisprudential analysis. The Nigerian Electricity Regulatory Commission made the REFIT 2015 pursuant to Sections 32 and 96 EPSRA, which set out a renewable energy on-grid electricity target of 2000MW by 2020. However, the legal issues in the execution and implementation of the policy, regulatory and contractual framework have affected the deployment of renewable energy technology for on-grid electricity. Although 13 PPAs were executed by NBET and the IPPs for the development of 13 solar power plants, Clause 1 of the PPAs enjoined parties to execute necessary financial documents, such as Put-Call-Options Agreements (PCOAs) and Partial Risk Guarantee Agreements (PRGA) and required approvals obtained before the PPAs could be enforced. The Federal Government refused to execute the PCOAs with the IPPs, due to disputes regarding the applicable tariff. The PCOAs were later signed for two PPAs, but the requisite approval was not obtained from the Attorney General of the Federation. International Financial Institutions also reneged on executing the PRGA due to the liquidity crisis in the power sector. The foregoing prevented the PPAs from reaching financial closure. As a result, investors were discouraged from investing in renewable electricity technology in Nigeria. The efforts of Nigerian government to boost electricity generation and achieve the target energy-mix and tariff structure have not been realised due to the regulatory impediments that have made it impossible to implement the 13 PPAs. Government agencies should honour contractual obligation and comply with established regulations.